2017
DOI: 10.1055/s-0036-1597839
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Transarterial Embolization for Blunt Abdominal Injuries: A Multicenter Study with Review of Literature

Abstract: Aims To evaluate the safety and effectiveness of transarterial embolization for blunt abdominal trauma in patients without the imaging signs of peritonitis or bowel injury. Materials and Methods A total of 45 patients (41 males and 4 females; mean age: 32.15) were studied, of which 48% were hemodynamically unstable. All patients underwent multidetector computed tomography prior to selective angiography and embolization. Outcomes were considered as favorable if embolization was successful in achievi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…However, their mean length of stay was 5.2 days while our BT cohort was 13.7 days. 10 Hemodynamic instability is an indication for operative management of BT; Cherian et al corroborates with our study that shows that a high rate of success for embolization persists among patients with upper abdominal BT. It is also effective for lower abdominal BT; Bertelli et al demonstrated this in a case series of mesenteric bleeding among patients with BT.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, their mean length of stay was 5.2 days while our BT cohort was 13.7 days. 10 Hemodynamic instability is an indication for operative management of BT; Cherian et al corroborates with our study that shows that a high rate of success for embolization persists among patients with upper abdominal BT. It is also effective for lower abdominal BT; Bertelli et al demonstrated this in a case series of mesenteric bleeding among patients with BT.…”
Section: Discussionsupporting
confidence: 89%
“…However, their mean length of stay was 5.2 days while our BT cohort was 13.7 days. 10 Hemodynamic instability is an indication for operative management of BT; Cherian et al They have demonstrated that decisions regarding which artery to embolize and the embolics used are decided during the procedure; an interventionist should have gelfoam, coils, and glue ready to be selected and used for embolization. They also recommend using angiography prior to embolization to plan access to distal feeding arteries.…”
Section: Discussionmentioning
confidence: 99%
“…Among the hepatic vascular lesions, about 85% are caused by trauma (Monsignore et al 2012 ); more than 80% of the hepatic lesions related to trauma can be treated with non-surgical interventions, such as clinical/radiological control (Petrowsky et al 2012 ; Leppaniemi et al 2011 ; Cherian et al 2016 ). Embolization represents a significant number in non-surgical therapy, especially in patients with grade IV and V liver trauma, with high rates of success, with 97% of technical success at the end of the procedure (Ierardi et al 2016 ; van der Wilden et al 2013 ; Stassen et al 2012 ; Monnin et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%